2015
DOI: 10.4330/wjc.v7.i3.150
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of secundum type atrial septal defects: More than 5-year follow-up

Abstract: Percutaneous ASD closure has good long-term safety and efficacy profiles. The residual RLS rate seems to be high more than 5 years after closure, especially in the CS/SF. Residual LRS was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…However, as in our case, TTE may not reveal displaced devices or even remaining defects in the PFO. Accordingly, a recent follow-up study concluded that devices evaluated > 5 years after closure with TTE were well placed ( 33 ), but two patients in this population had their devices surgically removed, and up to 45% had residual shunting when evaluated with contrast. While intracardiac ultrasound may be of help during the insertion of PFO devices ( 34 39 ), TEE remains the diagnostic “gold standard” for evaluating cardioembolic sources of stroke ( 40 44 ), and repeated prerequisite Valsalva maneuvers followed by contrast injections and careful evaluations are important to avoid misinterpretations and diagnostic failure ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as in our case, TTE may not reveal displaced devices or even remaining defects in the PFO. Accordingly, a recent follow-up study concluded that devices evaluated > 5 years after closure with TTE were well placed ( 33 ), but two patients in this population had their devices surgically removed, and up to 45% had residual shunting when evaluated with contrast. While intracardiac ultrasound may be of help during the insertion of PFO devices ( 34 39 ), TEE remains the diagnostic “gold standard” for evaluating cardioembolic sources of stroke ( 40 44 ), and repeated prerequisite Valsalva maneuvers followed by contrast injections and careful evaluations are important to avoid misinterpretations and diagnostic failure ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, AF occurred at similar rates after PFO closure with Amplatzer® devices (St. Jude Medical, Plymouth, MN, USA) compared with medical therapy in the RESPECT (Randomized Evaluation of Recurrent Stroke Comparing PFO Closure to Established Current Standard of Care Treatment) trial (2.9% vs. 1.0%; P = 0.16) and in the PC trial (Clinical Trial Comparing Percutaneous Closure of Patent Foramen Ovale Using the Amplatzer PFO Occluder with Medical Treatment in Patients with Cryptogenic Embolism) (3% vs. 1.5%; P = 0.13) ( 50 , 73 ). However, uniformly comparable heart rhythm monitoring before device closure was not available in any of the studies, and recent follow-up studies of “atrial septum defects closed with devices” demonstrate a high risk (6.6–17.9%) of AF in the first year after the procedure, decreasing to negligible (0–3.9%), but with only 76–82% of the original population included in one study ( 33 , 74 , 75 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplatzer Septal Occluder is a catheter-based ASD closure device that consists of a self-expanding double-disk nitinol mesh that apposes both sides of the septal wall (Fig 8a). The Amplatzer Septal Occluder has shown high closure rates, with low residual shunting at 5-year followup (27). The device comes in multiple sizes and may also be used for muscular ventricular septal defect (VSD) occlusion.…”
Section: Device and Radiographic Appearance-thementioning
confidence: 99%
“…Atrial septal defects (ASDs) are a common cardiac congenital finding with complications due to the left-to-right shunt (LRS). Percutaneous closure of an ASD is considered to be the first choice and has been proven safe and effective using different devices [1,2]. Worldwide, there is a lot of good experience with the Amplatzer septal occluder.…”
Section: Introductionmentioning
confidence: 99%